Pemetaan Sumber Daya Lokal Kota Pekalongan untuk Mendukung Kebutuhan Kawasan Industri Terpadu Batang - Musyarofah, Siti Afiani; Tontowi, Alva Edy (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2024)
The establishment of the Kawasan Industri Terpadu Batang (KITB) opens up economic opportunities by absorbing labor and fulfilling needs based on local resources. Pekalongan City, which is adjacent to KITB, has the opportunity to gain financial and social benefits, reduce disparities in regional development, and increase Gross Regional Income (GRDP). However, Pekalongan City does not yet have a comprehensive map of resource potential that meets KITB's needs. This study aims to build a more comprehensive map of Pekalongan City's Resource potential according to KITB's needs. Descriptive qualitative analysis is used to analyze the multiplier effect of KITB and social mapping for mapping human resources according to KITB's needs. Meanwhile, quantitative analysis with shift-share and location quotient is used for its economic analysis. Finally, a SWOT analysis is carried out to describe the development strategy for local resource potential in Pekalongan City. The results of the study indicate that there are four (4) leading and potential sectors to be developed as drivers of the economy in Pekalongan City: (1) Accommodation and food and beverage provision; (2) Water supply; Waste, waste, and recycling management; (3) Construction; and (4) Health services and social activities. Based on the results of the multiplier impact analysis, there are 10 business sectors in Pekalongan City that are very closely related to the needs of KITB, such as the processing industry, creative industry, provision of accommodation and food and beverages, and others. 56.89% of the openly unemployed workforce in Pekalongan City have the opportunity to be absorbed as workers in various KITB industry tenants and with the skills they have and have been adjusted to the needs of 18 companies: sewing/garment skills, informatics, construction, and welding. In addition, several strategies were proposed by the Pekalongan City Government to develop the potential of local resources.